Pengaruh Kemampuan Berbahasa Asing terhadap Prestasi Akademik dan Non Akademik Siswa di beberapa Sekolah di Kota Mataram - Rizky Ananda Purnomo; Dewi Lestari Putri (Journal of Language Studies, 2026)
Foreign language proficiency has become a crucial competence for students in the context of globalization and educational competitiveness. This study aims to examine the influence of foreign language skills on students’ academic and non-academic achievement. A quantitative correlational research design was employed involving 180 senior high school students selected through proportional random sampling. Data were collected using standardized foreign language proficiency tests, academic achievement records, and questionnaires measuring non-academic achievement, including participation in competitions, leadership activities, and extracurricular involvement. The data were analyzed using descriptive statistics, Pearson correlation, and multiple regression analysis. The results indicate a significant positive relationship between foreign language proficiency and academic achievement (r = 0.62, p < 0.01) as well as non-academic achievement (r = 0.58, p < 0.01). Regression analysis shows that foreign language proficiency significantly predicts both academic and non-academic outcomes. These findings suggest that students with higher foreign language competence tend to demonstrate better academic performance and greater engagement in non-academic activities. The study concludes that strengthening foreign language education can contribute to holistic student development. The results provide empirical evidence for policymakers and educators to integrate foreign language learning as a strategic component in improving educational quality.